Green marketing orientation impact on business performance: Case of pharmaceutical industry of Pakistan - Shaukat, Fatima; Ming, Jia (Frontiers in Psychology, 2022)
The present study is based on the natural resource based view which examines the impact of holistic marketing orientation over the business performance (BP) by elaborating the role of enablers and mediator. The drivers including corporate social responsibility (CSR) and environmental culture (EC) influence are whereby tested by analyzing the role of sustainable competitive advantage (SCA) as mediator. The analysis is based on the 299 samples collected from top and middle level managers of pharmaceutical industry. The structural equation modeling is done using Smart PLS 3.2.8. The research outcomes reveal that corporate social responsibility and environmental culture have a substantial impact on green marketing orientation (GMO). The results shows that there is significant direct and indirect impact of GMO on business performance while a full mediation of sustainable competitive advantage exists between the green marketing orientation and business performance. The outcomes facilitate the managers in the decision making about green marketing strategy for the long term three fold benefits besides strengthening their competitiveness.